Apple, Inc. : data privacy and a request from the FBI - Baily, Cory (SAGE Knowledge. Cases., 2017)
The case centres on the aftermath of a terrorist attack in 2016 when Syed Farook and his wife attacked a festival in San Bernardino. After the shooting, searches revealed just one significant piece of electronic evidence that had not been destroyed, shooter Syed Farook's employer-issued iPhone 5c running iOS 9. But the FBI could not unlock the phone to continue with their investigation and asked Apple to disable the auto-erase function on the iPhone so that the FBI would be able to submit multiple passcodes to the device for testing. Apple refused to comply with the FBI's request and a court order was issued ordering Apple to help the FBI hack into Farook's phone. The study invites the student to consider how the ethos of company, namely Apple's commitment to protecting the privacy of its customers and the law can come into conflict.